On Replication in Communication Science. Issue 3 (27th May 2018) - McEwan, Bree; Carpenter, Christopher J.; Westerman, David
Abstract : Replications are an important part of the research process because they allow for greater confidence in the findings of communication research. However, engaging in replications is often undervalued, replication studies can be difficult to publish, and thus it is difficult for individual scholars to devote their resources toward replication. This essay outlines the importance of replications for communication science and provides a framework for this special issue on replications. The authors also issue a call for communication scholars to consider future projects and structural changes that would incentivize future replication studies. Abstract :